Klasifikasi Data Penduduk Untuk Menerima Bantuan Pangan Non Tunai Menggunakan Algoritma Naïve Bayes - Nurahman Nurahman; Muhammad Mastur Alfitri; Eddy Mashamy (STMIK Budi Darma, 2022)
Indonesia's population reaches 273,879,750 people, and it is known that every year it is increasing, so that population movements begin to occur from island to island. The population movement is carried out by everyone with the aim of getting a job to fulfill the necessities of life. However, not all of them can be fulfilled, even though there are still people who fall into the poor category, one of which is part of the population in the village of Bapinang Hulu. In the Bapinang Hulu village there is a Non-Cash Food Aid which is used to help the poor. The Non-Cash Food Assistance Program for the poor should be carried out with the right target. To overcome this, it is necessary to analyze population data. The analysis was carried out using the Nave Bayes Algorithm by dividing the dataset into training data and testing data. Testing the data 9 times to determine the accuracy of the results of research analysis in the search for the Accuracy performance vector value. The results showed that the accuracy performance vector value reached 90.00%. So it is known that the Naive Bayes algorithm is able to analyze population data for determining Non-Cash Food Aid in the upstream bapinang village.